Economic Effectiveness Evaluation in a Project of Information Technology Change on the Example of Order Processing System - Dyczkowski, Mirosław (Advanced Information Technologies for Management – AITM 2008, 2008)
One of the most common groups of IT projects comprise undertakings which nature lies in change of used technologies. Such initiatives aim at substituting existing systems for solutions characterised by better technical parameters, higher utility or technological compatibility with other applications in a business environment. These projects, as all the other undertakings in informatisation field, must be economically effective. Therefore a profitability analysis is required, before they are initiated. This paper presents methodological grounds for such an analysis and introduces a procedure of effectiveness evaluation which is consistent with requirements of the so-called European projects. The main part of the work includes an example of economic effectiveness evaluation for a project which involved an improvement of an order processing system. The project was carried out by one of the main food articles suppliers for major retail chains, and aimed at substituting existing business document exchange technology for solutions based on e-EDI.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 67-78